Microstructural evolution and wear performance of the high-entropy FeMnCoCr alloy/TiC/CaF2 self-lubricating composite coatings on copper prepared by laser cladding for continuous casting mold. Issue 10 (6th March 2019) - Jiang, Jun; Li, Ruidi; Yuan, Tiechui; Niu, Pengda; Chen, Chao; Zhou, Kechao
Abstract: Abstract : The FeMnCoCr high-entropy alloy/TiC/CaF2 self-lubricating coatings were successfully prepared on a Cu–Zr–Cr alloy for continuous casting mold by laser cladding for wear-resistance. The intriguing finding was that the laser-cladded FeMnCoCr is mainly composed of face-centered cubic and hexagonal close-packed solid solution phases. During the cladding process, the FeMnCoCr/TiC or the FeMnCoCr/TiC/CaF2 mixed sufficiently with Cu matrix, while FeMnCoCr exhibited a spherical shape owing to being insoluble in Cu. The average hardness of the FeMnCoCr/TiC/CaF2 self-lubricating high-entropy alloy (HEA) coatings was twice that of the pure FeMnCoCr HEA coating. By addition of TiC, the friction coefficient and wear rate were decreased from 0.35 and 3.68 × 10 −15 mm 3 /m to 0.27 and 3.06 × 10 −15 mm 3 /m, respectively. When CaF2 was added, the friction coefficients and wear rate were decreased to 0.16 and 2.16 × 10 −15 mm 3 /m, respectively, which was 54% lower than the pure FeMnCoCr HEA coating. The main wear mechanism of the FeMnCoCr coating is abrasive wear while that of the FeMnCoCr/TiC coating is abrasive and adhesion wear. But adhesion wear is dominant for the FeMnCoCr/TiC/CaF2 coating.